The Institute of Internal Auditors: 50 Years of Progress Through Sharing. - Schneider, Arnold; Moriarity, Shane R. (The Accounting Review, 1992)
Reviews the book `The Institute of Internal Auditors: 50 Years of Progress Through Sharing,' by Dale Flesher.